Transcriptomic analysis reveals novel molecular signaling networks involved in low voluntary running behavior after AP-1 inhibition. (15th January 2023) - Mao, Xuansong; Grigsby, Kolter B.; Kelty, Taylor J.; Kerr, Nathan R.; Childs, Thomas E.; Booth, Frank W.
Highlights: AP-1 in nucleus accumbens (NAc) regulates voluntary wheel running behavior. Decrease in running distance was observed in WT following AP-1 inhibition. Running distance was increased following AP-1 inhibition in LVR. Differential molecular changes following intra-NAc's AP-1 inhibition in WT vs LVR. AP-1 inhibition may be the key to rescue low physical activity level. Abstract: Understanding the neuro-molecular mechanisms that mediate the quantity of daily physical activity (PA) level is of medical significance, given the tremendous health benefits associated with greater physical activity. Here, we examined the effects of intra-nucleus accumbens (NAc) inhibition of activator protein-1 (AP-1), an important transcriptional factor downstream of cAMP response element binding protein (CREB; a reward-related transcriptional regulator), on voluntary wheel running behavior in wild-type (WT) and low voluntary running (LVR) female rats. Transcriptome analysis of the nucleus accumbens (NAc; a brain region critical for PA reward and motivation) was performed to further determine molecular responses to intra-NAc AP-1 inhibition in these rat lines. Within WT rats, intra-NAc AP-1 inhibition caused a significant decrease in overnight running distance in comparison to control rats ( p = 0.009). Transcriptomic and bioinformatic analysis in WT rats identified involvement of gene products that regulate cellular proliferation and development, which were cellular processes regulated by AP-1. In contrast to above decreased WT distances, intra-NAc AP-1 inhibition in LVR rats increased nightly running distance in comparison to LVR control rats ( p = 0.0008). Further analysis identified gene products that are associated with regulating intracellular Ca 2+ homeostasis, calcium ion binding and neuronal excitability. In short, our study aims to gain a comprehensive understanding of transcriptional profile that was due to AP-1 inhibition in NAc, in which it could not only enhance the knowledge regarding molecular regulatory loops within NAc for modulating voluntary running behavior, but also provide further insights into molecular targets for future investigations.